An analysis of Fringe Suburb Residential Pattern: A Case Study of Madurai City, Tamil Nadu, India - Parthasarathy1, I.K. Manonmani1, S. Tamilenthi2*, G.R. (Journal of Experimental Sciences, 2011)
Rapid urban development and increasing land use changes due to increasing population and economic growth is being witnessed in India and other developing countries. The study area comprises of Madurai City and fringe villages. It extends geographically from 90 50’ North latitude to 10º North latitude and between 780 02’ East longitude and 78º12’ East longitude. primary data pertaining to the study period 2005-06 have been systematically collectedThe JPEG image file has been imported to Map Info 6.5. It is geo-referenced to fit into Map Info 6.5 GIS. These geographically rectified raster image maps are suitably converted to vector data format by means of on-screen digitization, and the resultant vector layer has been edited by using layer editable method. Simple overlay analysis has been performed to prepare final layouts and appropriate results were drawn.